Analyzing environment blogs on microblog - Tan, Han Meng. (2012)
For the past few years, environmental issue especially global warming is becoming a very concern topic on international level, this is due to the consistent apprehension and trepidation that the ozone layer may deplete even more causing extreme condition that is unbearable to all living things – including human.